Risk factors associated with speech and language impairment at 4-5 years of age - Harrison, L; McLeod, S (My University, 2007)
Speech and language disorders in children are not usually diagnosed until after 3 years of age, so identifying risk and protective factors would be of great benefit for early intervention programs. Using data from the wave 1 preschool cohort of 'Growing Up in Australia, the Longitudinal Study of Australian Children' (LSAC), the authors examine whether there are significant child, parent or family predictors for speech and language difficulties or speech pathology service usage. The authors also note the discrepancies between previous studies on risk factors.
Keywords: Child Development -- Speech and Language; Child Development; Childhood and child development; Child Development; Speech and Language; Childhood and child development